Dynamics of Single Pt Atoms on Alumina during CO Oxidation Monitored by Operando X‑ray and Infrared Spectroscopies - Dessal, Caroline; Len, Thomas; Morfin, Franck; Rousset, Jean-Luc; Aouine, Mimoun; Afanasiev, Pavel; Piccolo, Laurent (ACS catalysis, 2019)
Single-atom catalysts (SACs) are promising atom-efficient materials, with potentially superior performances with respect to their nanoparticulate counterparts. Because of its practical importance and relative simplicity, CO oxidation on Pt/γ-Al2O3 is considered as an archetypal catalytic system. The efficiency of the corresponding SAC has recently been the subject of debate. In this work, in addition to systematic high-resolution scanning transmission electron microscopy, we have simultaneously monitored the Pt dispersion, oxidation state, and CO oxidation activity by operando fast X-ray absorption spectroscopy and diffuse reflectance infrared spectroscopy, both combined with mass spectrometry. It is shown that single Pt m+ atoms (m ≥ 2), resulting from the standard impregnation–calcination procedure of SAC preparation, are poorly active. However, they gradually and irreversibly convert into highly active ∼1 nm sized Ptδ+ clusters (δ < 2) throughout the heating–cooling reaction cycles, even under highly oxidizing conditions favorable to atomic dispersion. An increase in the Pt loading or the CO/O2 concentration ratio accelerates the clustering–reduction phenomena. This work not only demonstrates a gradual aggregation−activation process for an important catalytic system but also highlights the power of operando spectroscopies to address stability issues in single-atom catalysis.